Possibilities of Increasing the Efficiency of Production Systems by Using an Additional Capacitive Element - Michlowicz Edward (Management Systems in Production Engineering)
The continuity of the flow of materials needed for correct operation of manufacturing systems can be achieved using different means and control methods. These objectives can be achieved through the use of Total Productive Maintenance (TPM). Specific effects can also be achieved by using additional capacitive elements in device systems (manufacturing lines). In this paper to be considered is a system with a serial structure and an additional capacitive element (the position within the system and the capacity of the element are determined). The capacitive element divides the system into two subsystems: the part delivering the material to the buffer (DP) and the part receiving the material (RP). The time lost due to unplanned interruptions in the operation of the production system equipment is described by the MTTR (Mean Time to Repair) indicator. The analysis of the system’s operation used the failure index, which is directly related to the MTTR index. To study the system, a method involving the analysis of states and a digital simulation are used. To assess the system with an additional capacitive, a production performance indicator is used. The obtained results allow for conclusions on the possibilities for improving the effectiveness of manufacturing systems using the proposed method.